Peran Kapabilitas Teknologi Pada Inovasi Berkelanjutan: Sebuah Literatur Review Tahun 2020-2024 - Nuraidya Fajariah; Isti Fadah; Via Lailatur Rizki (Journal of Creative Power and Ambition (JCPA), 2025)
This research aims to explore studies on technology capability in eco-innovation and the role of corporate technology capability in supporting the emergence of sustainable innovation in companies during the period 2020-2024. This research uses a Systematic Literature Review approach. (SLR). This research examines relevant literature to understand the extent to which technological capabilities influence sustainable innovation. The literature examined in this study consists of journal articles indexed in Scopus for the period 2020-2024. There were 64 pieces of literature found, then a thorough screening was conducted, resulting in 15 pieces of literature that met the criteria. The study results indicate that technological capabilities play a role in supporting various aspects of sustainable innovation such as improving operational efficiency, collaboration with external parties, waste reduction, and compliance with environmental regulations. Furthermore, the findings indicate that technological capabilities drive companies to innovate, both radically and incrementally. This research concludes that technological capabilities are a key element for companies to overcome global challenges and enhance competitiveness through sustainable innovation.